The Effect of Probiotic Use on Some Blood Parameters in Overweight and Obese Women Who Follow a Weight-Loss Diet: The Probiotic Use on Overweight and Obese Women Following a Weight-Loss Diet - İşgüzar Orak, Yeşim; Bulduk, Sıdıka; Baştemir, Mehmet (Progress in Nutrition, 2022)
Background and aim: This study was conducted to determine the effect of 8-week probiotic use on body composition and blood parameters in overweight and obese women who are on a weight loss dietMethods: 34 women with a BMI value above 25 kg/m2 participated. The individuals participating in the research were divided into two groups. For eight weeks, the experimental group was given a weight loss diet program, exercise program and oral probiotic nutritional supplement containing various probiotic strains in the amount of 1.5x109 cfu/g in each capsule twice a day; The control group was given a weight loss diet program and an exercise program without probiotic supplementation. Anthropometric measurements of the individuals (height baseline, body weight, waist, hip and neck circumference, body mass index, waist/hip circumference and waist-height ratio) in both groups were evaluated statistically at the initial, 4th and 8th weeks. Some biochemical parameters were measured at the beginning of the study and the end of the 8th week.Results: A significant difference was found between body weight, body mass index, waist circumference, hip circumference, waist-height ratio, body fat percentage, and body fat mass measurements (p